Modelling hauler movement in a distributed simulation of earthmoving operations. (2016) - Li, Duanshun; Petre, Cristian; Kerr, Cayce; Joseph, Tim; AbouRizk, Simaan; Mohamed, Yasser
As critical components of mining and construction projects, earthmoving operations utilise heavy equipment to execute excavation, loading, hauling, dumping, grading, and compacting tasks in a repetitive and almost continuous manner. Previous models tend to simulate these operations at a higher level, which ignores various independent factors such as road layout, road material, road maintenance frequency, trucks and excavator characteristics, and weather conditions, which will affect the efficiency, environment and the capital cost continuously and dynamically. To incorporate various independent factors and models into the simulation platform, the simulation presented herein is developed with a distributed approach using high level architecture (HLA) standards to enable inclusion of different comprehensive models and behaviours that affect these operations. This paper presents the design and development of a comprehensive simulation of earthmoving operations and the components of the simulation and models implemented in each, with a major focus on the transportation and hauling component. It also describes the distributed development process and showcases the implementation outcomes and sample use and validation of the simulation.